PENGARUH DESENTRALISASI PENGAMBILAN KEPUTUSAN DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA SATUAN KERJA PERANGKAT DAERAH DENGAN SISTEM PENGENDALIAN AKUNTANSI SEBAGAI VARIABEL INTERVENING (Studi Pada Pemerintah Daerah Kabupaten Bungo) - Sri Wineh (Jurnal Akuntansi & Keuangan Unja, 2015)
The aim of this research are (1) to examine the effect of decentralization of decision making  and perceived  environmental uncertainty  on accounting control system, (2)  to examine the effect of decentralization of decision making  and perceived  environmental uncertainty  on managerial performance, (3) to examine the effect of accounting control system on managerial performance, (4) to examine accounting control system as the intervening variable on the relationship betwen decision making decentralization and perceived  environmental uncertainty uncertainty  on managerial performance .The study population was a goverment office in Kabupaten Bungo. Sample research is heads of offices, middle managers and low managers of the goverment office. Data were collected through questionnaires, out of 110 questionnaires sent, only 84 questionnaires could be processed. Testing data using multiple regression analysis extended with the path analysis. The results of this study indicate that the effect of decentralization of decision making and perceived enviromental uncertainty on accounting control system (H1), decentralization of decision making and perceived enviromental uncertainty on accounting control system  influence on managerial performance (H2). Accounting control system influence on managerial performance (3). Decentralization of decision making and Environmental uncertainty had no effect on managerial performance through the use of accounting control systems (H4). That means, the linkage of decentralization of decision making and perceived enviromental uncertainty is indirect influence with managerial performance.  It can be concluded that of the four hypotheses only hypothesis 1, 2 and 3 are acceptable while the other hypotheses are rejected